Disseminated cat‐scratch disease presenting as nausea, diarrhea, and weight loss without fever in a heart transplant recipient. Issue 3 (26th May 2017) - Antar, Annukka A. R.; Goyal, Amit; Murphy, Karly; Schimmel, Matthew; Gilotra, Nisha A.; Martin, Isabella; Crane, Genevieve Marie; Sciortino, Christopher; Avery, Robin K.; Houston, Brian A.
Abstract: We report the case of an afebrile 59‐year‐old heart transplant recipient presenting with nausea, vomiting, diarrhea, weight loss, and diffuse lymphadenopathy. Lymph node biopsies revealed non‐caseating granulomatous inflammation. Cat‐scratch disease was confirmed by serologic studies, Warthin‐Starry staining, and polymerase chain reaction testing of lymph node tissue. The patient's symptoms resolved with 3 months of doxycycline. We review clinical presentations of Bartonella henselae infection and review diagnostic approaches for B. henselae in this patient population.